Identifying autism spectrum disorders in school children for placement using a valid screening instrument in Nigeria - Adebisi, Rufus Olanrewaju; Igwe, Eucharia Nwakaego (Universitas Negeri Padang, 2020)
The purpose of this study is to identify and analyze the Autism Spectrum Disorders (ASD) using Childhood Autistic Rating Scale (CARS). This research was also conducted as an effort to carry out placement and intervention in special schools. Samples of this study is 52 subjects randomly selected from the population of 138 were used to rate their behaviours using the CARS. Method that used in this study is cross-categorical survey (descriptive research). This is a survey that studies a group of sample in order to identify traits of such group. With the use of statistical data of chi-square, scores collected from the participants revealed that there was no significant difference in the scores or ratings. Also, the result obtained from the use of t-test indicated that the instrument significantly differentiate ASDs traits from Non-ASDs. The findings in this study prompted a suggestion that special schools, centres, homes etc should get this valid instrument handy for the purpose of identifying autistic traits in school children for correct placement and intervention.